2014
DOI: 10.3390/s140202860
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hardware Implementation of the Horn-Schunck Algorithm for High-Resolution Real-Time Dense Optical Flow Sensor

Abstract: This article presents an efficient hardware implementation of the Horn-Schunck algorithm that can be used in an embedded optical flow sensor. An architecture is proposed, that realises the iterative Horn-Schunck algorithm in a pipelined manner. This modification allows to achieve data throughput of 175 MPixels/s and makes processing of Full HD video stream (1, 920 × 1, 080 @ 60 fps) possible. The structure of the optical flow module as well as pre- and post-filtering blocks and a flow reliability computation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In contrast, the benefit of using parallelism due to pipelining is illustrated by Komorkiewicz et al [8]. Although the approach is similar to the parallel approach which is presented here, the performance is worse.…”
Section: Recent Workmentioning
confidence: 66%
“…In contrast, the benefit of using parallelism due to pipelining is illustrated by Komorkiewicz et al [8]. Although the approach is similar to the parallel approach which is presented here, the performance is worse.…”
Section: Recent Workmentioning
confidence: 66%
“…Its operation is entirely based on the video frames of moving objects. (7,8) In our proposed aquarium for displaying 3D holograms of robot fish, to make the captured video smoother, we used the optical flow algorithm shown in Fig. 2.…”
Section: Optical Flow Detection Algorithmmentioning
confidence: 99%
“…Furthermore, the study [20] showed that pipelined image processing systems can achieve linear acceleration. Outstanding computing performances of parallel-pipelined modules for the Horn-Schunck optical flow algorithm were demonstrated in papers [31,35].…”
Section: Pipeline Data Processingmentioning
confidence: 99%
“…First, because it is consistent with the data sending method from the image sensor, and therefore frame buffering between successive operations is not required. Second, as already mentioned, the linear acceleration in a pipeline system [20] allows to achieve very high computing performance (operations per second) and energy efficiency (operations per watt) [31].…”
Section: Pipeline Data Processingmentioning
confidence: 99%
See 1 more Smart Citation